The Effect of Digital Learning, Innovative Behavior and Knowledge Management on Private Higher Education Performance - Muhammad Ramaditya; Syamsari Syamsari; Hadirawati Hadirawati; Alya Hanifah (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aimed to assess the impact of digital learning, innovative behaviour, and knowledge management on organisational performance, with the quality of education as a mediator, at private institutions in the LLDikti III area. The method used in this study was correlational, and the data were obtained through a questionnaire. The study focused on lecturers from private universities in the LLDikti III area.   The study included a total of 376 participants.   The analysis was conducted using SmartPLS 3, employing the Structural Equation Modelling technique based on Partial Least Squares.   The study findings indicate that digital learning has a direct impact on performance, innovative behaviour has a positive influence on performance, knowledge management affects performance, digital learning affects quality, innovative behaviour does not impact education quality, knowledge management affects education quality, and education quality influences organisational performance.  Through mediation or indirectly, digital learning influences organizational performance mediated by the quality of education; innovative behavior does not affect organizational performance mediated by the quality of education, and knowledge management influences organizational performance mediated by the quality of education in private universities.